Women in business and management: the business case for change (Geneva, 2019)
"Enterprises globally recognize the imperative of having a gender diverse workplace, including the integral benefits of having women in top decision-making positions. Mounting evidence shows that achieving gender balance and diverse management teams at all levels deliver positive business outcomes. The second edition of Women in business and management explores the business case for gender diversity in the workplace, women’s representation at management and board level and the various success factors that drive enterprise behaviour for inclusion. The report adds to the growing body of evidence that shows many enterprises are actively pursuing initiatives to boost the number of women in their talent pool but also shows that these efforts alone are insufficient. Enterprises still need to translate their policies into concrete action and critically address gender diversity within their organizational culture."